Evaluation of food storage racks available on the Polish market in the hygienic context - Wiesława Grzesińska; Marzena Tomaszewska; Beata Bilska; Joanna Trafiałek; Michał Dziadek (National Institute of Public Health - National Institute of Hygiene, 2018)
Background. Providing safe food products to the consumer depends on the material and technology used and adherence to hygienic practices, throughout the production process. The degree of microbial contamination of a surface is an important indicator of equipment cleanliness and effectiveness of cleaning and disinfection. Used material, construction solutions and quality of the applied devices also have an effect on hygienic status. Objective. The objective of the present study was to evaluate the influence of the design and construction material of selected food storage racks, available on the Polish market, on their hygienic status. Material and methods. The study was based on determination of the capability of microbial growth on the surface of the racks and the effectiveness of their cleaning. Microbiological cleanliness on the surface of the racks was monitored by the contact plates which are able to estimate the total number of icroorganisms. Examination of effectiveness of cleaning was conducted by the use of ATP bioluminescence method. Results. This experiment has proven a significant influence of adopted construction solutions on the hygienic status of the examined racks. Presence of antibacterial layer and a choice of the appropriate construction material characterized by a low surface roughness impedes the microbial growth and increases the effectiveness of cleaning. Conclusions. Design solutions have significant impact on the hygienic status of shelves. Selection of a suitable material for the construction of racks can greatly reduce the possibility of the development of microorganism, despite the low efficiency of the cleaning. The application of antimicrobial coatings inhibits microbial growth.